2002
DOI: 10.1088/0953-8984/14/6/307
|View full text |Cite
|
Sign up to set email alerts
|

Alternating-current conductivity and dielectric properties of Ge25Sb15-xBixS60bulk and thin-film glasses

Abstract: The effect of the replacement of antimony atoms by bismuth atoms on the electrical properties of compounds of the melt-quenched and thermally evaporated Ge25Sb15-xBixS60 (x = 0, 5, 10 and 15) chalcogenide system are reported for the first time. The results for the alternating-current (ac) conductivity σac and the dielectric constant ϵ1 of some bulk and thin-film samples of the four different compositions are presented over the temperature range 134-373 K and the frequency range 0.1-100 kHz. The ac conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Relaxation mechanisms are for the most part two sorts to be specific (i) quantum-mechanical tunneling (QMT) through the barrier and (ii) classical hopping over the barrier [74,75]. The QMT conduction of charge carriers through barriers separating localized mechanism is not applicable in this ZnO NPs sample because s is depending on temperature in this experiment [76]. Velayutham et al also observed the CBH in the ZnO NPs sample and they explain the differences between CBH and QMT in semiconducting ZnO nanosystems [77].…”
Section: Conductivitymentioning
confidence: 98%
“…Relaxation mechanisms are for the most part two sorts to be specific (i) quantum-mechanical tunneling (QMT) through the barrier and (ii) classical hopping over the barrier [74,75]. The QMT conduction of charge carriers through barriers separating localized mechanism is not applicable in this ZnO NPs sample because s is depending on temperature in this experiment [76]. Velayutham et al also observed the CBH in the ZnO NPs sample and they explain the differences between CBH and QMT in semiconducting ZnO nanosystems [77].…”
Section: Conductivitymentioning
confidence: 98%
“…The electrical conductivity of Ge-M-S (M = Bi or Sb) was the subject of many investigations [2][3][4][5][6][7]. Various mechanisms of conductivity in bulk and thin films of Ge x Sb 40−x Se 60 chalcogenides system have been suggested [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogenide glasses have attracted researchers' interest because of their potential use in opto electronic and technological applications such as photo resists, image storage, and memory switching. AC conductivity and dielectric measurements have been reported for a wide variety of amorphous Chalcogenide semiconductors [1][2][3][4][5][6][7] in order to understand the mechanisms of conduction processes in these materials and the types of polarization. Chalcogenide glasses with low phonon energies and high refractive indices were found to be efficient host materials for fiber-optics amplifiers and infrared lasers when doped with rare earth ion [8].…”
Section: Introductionmentioning
confidence: 99%